Alzheimer's disease biomarker roadmap 2020: Fluid biomarkers: Strategic roadmap for the translation of tau biomarkers in the clinic: An international task force. (7th December 2020) - Ashton, Nicholas J; Leuzy, Antoine; Karikari, Thomas K; Dodich, Alessandra; Boccardi, Marina; Barthel, Henryk; Bischof, Gerard N; Carrillo, Maria C; Chiotis, Konstantinos; Corre, Julie; Démonet, Jean‐François; Drzezga, Alexander; et al.
Abstract: Background: Though cerebrospinal fluid (CSF) Aβ42, p‐tau181 and t‐tau have been shown to increase diagnostic accuracy for early Alzheimer's disease (i.e. AD at the MCI stage), several challenges remain with respect to their routine clinical use. In order to address these and related issues, a multidisciplinary task force was formed (Geneva Biomarker Roadmap Initiative). Adapting a five‐phase framework for the development of cancer biomarkers (Pepe et al., 2001), this task force recently convened (2019) to provide an update on earlier publications (2017). We here provide an update for the core CSF AD biomarkers (Aβ42/Aβ40, p‐tau181 and t‐tau) and for the first time provide a review of the same measures in blood in context of the five‐phase framework. Method: In a two‐day workshop (Geneva, November 2019), we convened a panel of experts in AD biomarkers. The level of maturity of CSF and blood biomarkers was assessed based on the Biomarker Roadmap (Frisoni et al., 2017). Biomarker maturity and research priorities were systemically assessed by subgroups before the meeting, and presented and discussed during the workshop. Result: CSF biomarkers continued to demonstrate the highest level of maturity according to the strategic roadmap. Significant improvements compared to the 2017 summary (Mattsson et al., 2017) included the development of fully‐automated assays and the introduction of standard operating procedures for the preanalytical handling of CSF. Despite being in their infancy, the data presented and discussed for certain blood biomarkers demonstrated promising results. While t‐tau in blood did not satisfy the criteria for phase 2 (diagnostic discrimination), p‐tau181 and Aβ in blood either fully or partially fulfilled the criteria for this phase. It was agreed that only preliminary, albeit encouraging, evidence was available for the ability of blood measures to predict AD dementia in subjects with MCI (phase 3). An overview of novel CSF and blood tau biomarkers will also be discussed. Conclusion: The core CSF AD biomarkers (t‐tau, p‐tau181 and Aβ) have the highest level of maturity for clinical utility. Blood biomarkers for p‐tau18, and to a lesser degree Aβ, show excellent discrimination for AD from controls and non‐AD neurodegenerative disorders.